Green Synthesis and Characterization of Biosilica Produced from Sugarcane Waste Ash - Rodrigo Heleno Alves; Thais Vitória da Silva Reis; Suzimara Rovani; Denise Alves Fungaro (Journal of Chemistry)
In this study, ash from sugarcane waste was used in the synthesis of biosilica using alkaline extraction followed by acid precipitation. Different parameters that could influence the silica particle synthesis were evaluated. The ash and synthesized biosilica were characterized by a combination of spectroscopic and chemical techniques such as XRD, XRF, SEM, particle size analyser, N2 adsorption analysis, TGA, and FTIR. The best condition for biosilica production was achieved with fusion method and aging temperature of 80°C for 1 h during gel formation. X-ray powder diffraction pattern confirms the amorphous nature of synthesized silica. The purity of the prepared silica was 99% silica which was confirmed by means of XRF. The experimental data suggest that the sugarcane waste ash could be converted into a value-added product, minimizing the environmental impact of disposal problems.